APLIKASI FUZZY ANALYTICAL HIERARCHY PROCESS UNTUK MENENTUKAN PRIORITAS PELANGGAN BERKUNJUNG KE GALERI (Studi Kasus di Secondhand Semarang) - Agung Santoso; Rita Rahmawati; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Entrepreneur have an important role in the development of developing countries. Entrepreneurship has many responsibilities, one of them is in making decisions concerning organizational leadership, marketing and others. Making the right decisions to support advancement a company. Analytic Hierarchy Process (AHP) is a decision support models to find the order of priority of the various alternatives in solving a problem. Weakness contained in the AHP is subjectivity. The approach to the fuzzy concept can minimize these weaknesses. The use of function Triangular Fuzzy Number (TFN) on Fuzzy AHP can clarify uncertainties in the interval assessment scale. This study aims to identifies the priority of customers visiting the gallery case study in Secondhand Semarang. The data taken by distributing questionnaires to customers have ever visiting as respondents. The results showed criteria of Barang is a top of priority with the highest priority weight is 0,341. Criteria of Produk followed with 0,245 priority weight, then criteria of Suasana with 0,211 priority weight, and the last criteria of Lingkungan with 0,201 priority weight.